Inclusive leadership, safety climate and safety behaviour: a proposed framework - Bara, Kabaka Brown; Chandrakantan, Subramaniam; Ali, Hassan (Human Resource Management Academic Research Society, 2017)
The purpose of this paper is to propose a framework for understanding inclusive leadership as an antecedent of the safety climate – safety behaviour relationship.Though the relationship between safety climate and safety behaviour is well-established in the safety management literature, studies on the antecedents of safety climate are few.More so, while a few studies have examined leadership as an antecedent of safety climate, none has examined inclusive leadership in relation to safety climate and by extension, safety behaviour.Of note also is that no study has examined the direct relationship between inclusive leadership and safety behaviour.Hence, this paper discusses inclusive leadership as an antecedent of the safety climate-safety behaviour relationship.A conceptual model backed by the Social Exchange Theory is thus proposed for future empirical endeavours and for expanding the leadership and safety management literature.